Diagnostic efficiency of metagenomic next-generation sequencing for suspected spinal tuberculosis in China: A multicenter prospective study - Li, Yuan; Yao, Xiao-wei; Tang, Liang; Dong, Wei-jie; Lan, Ting-long; Fan, Jun; Liu, Feng-sheng; Qin, Shi-bing (Frontiers in Microbiology, 2022)
Background: The pathogens of suspected spinal tuberculosis (TB) include TB and non-TB bacteria. A rapid and effective diagnostic method that can detect TB and non-TB pathogens simultaneously remains lacking. Here, we used metagenomic next-generation sequencing (mNGS) to detect pathogens in patients with suspected spinal TB. Methods: The enrolled patients with suspected spinal TB were regrouped three times into patients with spinal infection and controls, patients with spinal TB and controls, and patients with non-TB spinal infection and controls. We tested the three groups separately by using mNGS and conventional detection methods. Results: Ultimately, 100 patients were included in this study. Pathogens were detected in 82 patients. Among the 82 patients, 37 had TB and 45 were infected with other bacteria. In patients with spinal infection, the sensitivity of the mNGS assay was higher than that of culture and pathological examination (P < 0.001, P < 0.001). The specificity of the mNGS assay was not statistically different from that of culture and pathological examination (P = 1.000, P = 1.000). In patients with spinal TB, no statistical difference was found between the sensitivity of the mNGS assay and that of Xpert and T-SPOT.TB. (P = 1.000, P = 0.430). The sensitivity of the mNGS assay was higher than that of MGIT 960 culture and pathological examination (P < 0.001, P = 0.006). The specificities of the mNGS assay, Xpert, MGIT 960 culture, and pathological examination were all 100%. The specificity of T-SPOT.TB (78.33%) was lower than that of the mNGS assay (100%) (P < 0.001). In patients with non-TB spinal infection, the sensitivity of the mNGS assay was higher than that of bacterial culture and pathological examination (P < 0.001, P < 0.001). The specificity of the mNGS assay was not statistically different from that of bacterial culture and pathological examination (P = 1.000, P = 1.000). Conclusions: Data presented here demonstrated that mNGS can detect TB and non-TB bacteria simultaneously, with high sensitivity, specificity and short detection time. Compared with conventional detection methods, mNGS is a more rapid and effective diagnostic tool for suspected spinal TB.